Analiza Pewnego Modelu Ciała Sprężysto-Lepkoplastycznego - Drescher, A. (Engineering Transactions, 1967)
This is a discussion of the behaviour of the rheologic model proposed by I. Kisiel [3], for an elastic-viscoplastic body. The physical equations are analysed showing that the location of the plastic element inside the viscoelastic model leads to considerable difficulties of their formulation and also to difficulties of analysis of the loading and unloading conditions and the neutral state. The analysis of the behaviour of the yield surface and the loading conditions is done for a one- dimensional state, that of pure shear, by means of programs for a given strain rate, stress (creep) and stress rate. It is found that the yield surface, considered to be a generalization of the yield limit depends on the history of stress and strain. A particular feature of the model is the occurrence, after complete unloading, of a residual state of self-stress producing further strain of the model in agreement with or opposite to the strain produced by initial stress. It is also shown that there is a simple geometrical interpretation of the behaviour of the model before and after it becomes plastic for composite states if the yield surface is analysed in the strain space.